2011
DOI: 10.1111/j.1442-200x.2011.03352.x
|View full text |Cite
|
Sign up to set email alerts
|

Do rates of arthritis and chorea predict the incidence of acute rheumatic fever?

Abstract: Most patients presenting with ARF have either joint symptoms or chorea, features that could be recognized by community health workers and individuals with limited medical training. The referral of patients presenting with these manifestations for further evaluation might improve detection rates of ARF in resource-limited countries and lead to improved estimates of disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The frequency of carditis in the present study was found to be 66%, which is consistent with earlier investigations that reported rates of 40–80% . The mitral valve was the most commonly involved valve (93.2%) in the present study, followed by aortic valvulitis in 32% of cases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The frequency of carditis in the present study was found to be 66%, which is consistent with earlier investigations that reported rates of 40–80% . The mitral valve was the most commonly involved valve (93.2%) in the present study, followed by aortic valvulitis in 32% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3]11 The frequency of carditis in the present study was found to be 66%, which is consistent with earlier investigations that reported rates of 40-80%. [12][13][14][15][16] The mitral valve was the most commonly involved valve (93.2%) in the present study, followed by aortic valvulitis in 32% of cases. This is concordant with other studies, 14,[17][18][19] although a few authors have stated that aortic involvement was the commonest.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a recent study, Tunks et al . [17] point out the difficulty in diagnosing chorea, as an isolated manifestation, as well as atypical joint abnormalities in countries with a high prevalence. The hospital has an Abnormal Movements Outpatient Clinic of the Department of Neurology to which patients with a suspected diagnosis of Sydenham chorea are referred for a proper differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%